BENTUK –TA DALAM KALIMAT BAHASA JEPANG - Elizabeth Ika Hesti Aprilia Nindia Rini (IZUMI, 2013)
-ta form in Japanese is identical with tenses. Although it has the same structure, but   -ta form is not only related to the tenses, but also with aspects and modalities. There are times when tenses and aspect can not be separated because it forms into one and at the same time both states the time, mainly seen in compound sentences. Keywords : shape-ta, time, aspect, modality